Parasitoid Wasp Community Dynamics in Vineyards Following Insecticide Application - Schindler, Bracha; Gavish-Regev, Efrat; Keasar, Tamar (Frontiers in Environmental Science, 2022)
In order to integrate parasitoid wasps in agroecosystems as biological control agents, we need to understand how insecticides affect the parasitoids in the crops and their surroundings. We investigated the non-target effect of Indoxacarb, an insecticide commonly used against European grapevine moth, on parasitoid wasp communities in wine vineyards. We focused on characterizing: 1. The dynamics of common wasp species, and 2. Wasp abundance and species richness in the vineyard center, edge, and nearby natural area. Seven vineyards, with neighboring natural areas, were sampled before, and up to two weeks after, Indoxacarb applications over two years. We expected initial negative effects of spraying in the vineyard with some effect of Indoxacarb drift into the natural habitat, followed by wasp recovery, first in natural areas, then at the vineyard edge and finally in the center. Sticky traps were hung at the vineyard edge and center to evaluate migration into and out of the vineyard. Vacuum sampling was used to obtain parasitoid total abundance and species richness, and the abundances of four common species (43% of the wasps collected). From the vacuum samples we found that total wasp abundance and richness declined after spraying in the vineyards' margins and center but rose over time in the natural area. Vineyard wasp abundance was restored to pre-spraying levels within two weeks. Among the abundant species, Trichogramma sp. and Telenomus sp., which parasitize lepidopteran hosts, declined after spraying, and Trichogramma sp. recovered more quickly than Telenomus sp.. Two other abundant species, Lymaenon litoralis and Oligosita sp., did not decline after spraying. In the sticky traps, wasp abundance increased at the vineyard edge but not center after spraying, suggesting that there was migration of wasps at the vineyard edge, into or out of the crop. The results indicate an effect of Indoxacarb on the parasitoid wasp community, particularly on parasitoids of lepidopterans, the target group of Indoxacarb. The results also indicate a potential for recovery of the parasitoid community through migration from neighboring natural vegetation.